Pendampingan skrining pertumbuhan dan perkembangan sebagai pendeteksian dini pada anak usia prasekolah - Anggraeni, Fitri; Meylawati, Luluk Eka; Astuti, Harwina Widya (JOURNAL of Public Health Concerns, 2025)
Background: National development is essentially the development of the whole person. Efforts to develop the whole person must begin as early as possible, namely from the time a person is still in the womb and during infancy. Child development services play a crucial role, as early detection of developmental disorders allows for appropriate intervention. Delayed detection and intervention of developmental disorders can hinder a child's development and reduce the effectiveness of therapy. Purpose: To provide knowledge on conducting growth and development screening in preschool children. Methods: This community service activity was conducted at Angkasa 1 Kindergarten, Jakarta, targeting preschool-aged children. It involved 60 second-year students from the Diploma III Nursing Program, Faculty of Health Sciences, Universitas Suryaya (UNSURYA), and teachers at Angkasa 1 Kindergarten. Participants for the growth screening were 54 children present at school on the day of the community service activity. The developmental screening used a Pre-Screening Development Questionnaire (KPSP) instrument adapted to the children's age. The implementation of the Growth and Development Screening Assistance program in Early Detection in Preschool Children is designed holistically to ensure that early detection is carried out effectively. Results: The mean age of respondents was 63.0 months with a standard deviation of 9.10 months, ranging from 37 to 75 months. The majority of respondents (25) were in the 61-72 month range (46.3%), with a majority of males (29) being male (53.7%), and the majority of growth measurement results were in the good nutritional status category (42) (77.8%). Conclusion: The community service activity provided significant benefits for students, teachers, and children. Students had the opportunity to directly implement the child growth and development screening process. For teachers, this activity provided understanding and improved skills in conducting growth and development screening for preschool children. Keywords: Early detection; Growth and development; Preschool children; Screening Pendahuluan: Pembangunan nasional pada hakekatnya adalah pembangunan manusia seutuhnya. Upaya membangun manusia seutuhnya harus dimulai sedini mungkin, yakni sejak manusia itu masih berada dalam kandungan dan semasa balita. Pelayanan tumbuh kembang anak memiliki peran yang sangat penting, karena deteksi dini terhadap kelainan tumbuh kembang memungkinkan pemberian intervensi yang tepat. Jika kelainan tumbuh kembang terlambat dalam pendeteksian dan intervensi, maka hal ini dapat menghambat perkembangan anak dan mengurangi efektivitas terapi. Tujuan: Memberikan pengetahuan dalam melakukan skrining pertumbuhan dan perkembangan pada anak prasekolah. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan di TK Angkasa 1 Jakarta dengan sasaran anak-anak usia prasekolah yang melibatkan 60 mahasiswa tingkat 2 dari Program Studi Diploma III Keperawatan FIKES UNSURYA serta guru-guru di TK Angkasa 1 Jakarta. Peserta untuk skrining pertumbuhan adalah 54 anak yang hadir di sekolah pada hari pelaksanaan kegiatan pengabdian kepada masyarakat. Melakukan skrining perkembangan menggunakan instrumen Kuesioner Pra Skrining Perkembangan (KPSP) yang disesuaikan dengan usia anak. Pelaksanaan program Pendampingan Skrining Pertumbuhan dan Perkembangan dalam Pendeteksian Dini pada Anak Usia Prasekolah dirancang secara holistik untuk memastikan deteksi dini dilakukan secara efektif. Hasil: Mendapatkan usia rata-rata responden adalah 63.0 bulan dengan standar deviasi 9.10 bulan dalam rentang 37-75 bulan. Sebagian besar usia responden dalam rentang 61-72 bulan sebanyak 25 (46.3%), mayoritas berjeniskelamin laki-laki sebanyak 29 (53.7%) dan sebagian besar hasil pengukuran aspek pertumbuhan dalam kategori status gizi baik sebanyak 42 (77.8% Simpulan: Kegiatan pengabdian kepada masyarakat telah memberikan manfaat yang signifikan bagi mahasiswa, guru, dan anak-anak. Mahasiswa berkesempatan untuk mengimplementasikan secara langsung proses skrining pertumbuhan dan perkembangan anak. Bagi guru, kegiatan ini memberikan pemahaman dan meningkatkan keterampilan dalam melakukan skrining pertumbuhan dan perkembangan anak prasekolah.